Comparison of the euploidy rate in preimplantation genetic testing for aneuploidy cycles following progestin-primed versus gonadotropin-releasing hormone antagonist protocol: a randomized controlled study - Lu Wang; Jing Yun Wang; Yuan Zhang; Chen Qian; Xiao Hui Wang; Ernest Hung Yu Ng; Ai Ai; Zhi Qin Chen (Reproductive Biology and Endocrinology)
Abstract Background Progestins can block endogenous luteinizing hormone secretion from the pituitary gland and have shown similar efficacy in terms of collecting competent oocytes and embryos; however, some inconsistencies have been proposed by the previous papers regarding the quality of oocytes and embryos obtained with the use of progestins. This study aimed to compare the euploidy rate between women treated with progestin-primed ovarian stimulation (PPOS) and the gonadotropin-releasing hormone (GnRH) antagonist protocol. Methods This is a prospective randomized study of 240 infertile women undergoing PGT-A between August 2021 and July 2023. Infertile women with advanced maternal age (38–45 years), recurrent pregnancy loss (≥ 2 or 3 consecutive miscarriages), and repeated implantation failure (≥ 4 embryos replaced or ≥ 2 blastocysts replaced without success) undergoing PGT-A cycles were included. Women were randomly assigned into the PPOS group (n = 120) or the antagonist group (n = 120) according to a computer-generated randomization list. Dydrogesterone 20 mg per day was given from the start of ovarian stimulation until the trigger day in the PPOS group. In the antagonist group, an antagonist 0.25 mg was given daily from the sixth day of ovarian stimulation until the trigger day. The primary outcome measure was the euploidy rate, defined as the number of euploid blastocysts per injected oocyte. Results No significant differences were observed in the demographic and ovarian stimulation characteristics between the two groups. The euploidy rate was comparable between the PPOS and antagonist group (12.5% vs. 16.0% respectively, P > 0.05). No significant differences were observed between the two groups in positive pregnancy test, clinical pregnancy, miscarriage, ectopic pregnancy, or live birth rates per transfer in the first frozen embryo transfer cycles. Conclusion Both PPOS and antagonist protocols had similar euploidy rates in PGT-A cycles. Trial registration Clinicaltrials. gov identifier: NCT04989348 ( https://www.clinicaltrials.gov/ ). Trial registration date: Clinicaltrials. gov: 30 July 2021.